A ADAPTATION TO, AND COPING WITH, CLIMATE CHANGE IMPECTS AND THREATS - Sotiroska, Kalina; Nuredin, Mensur; Sardzoska, Elisaveta; Kahvecı, Müedin (International Scientific Journal Vision, 2018)
The focus of this article is to examine the human adaptation to climate change impacts, and to understand the coping mechanisms with climate change. The impacts of climate changes, seen as threat and stressor, aff ect the ways of individual and community adaptation. Adaptation includes a wide range of responses including how people perceive, react and understand, that indicate how they behave in response to the problems. Psychologist can assist adaptive responses and help people in many ways to cope properly to changes. There is a need of new policy initiatives integrating psychological adaptation processes.